Multinational data on cumulative radiation exposure of patients from recurrent radiological procedures: call for action. - Brambilla, Marco; Vassileva, Jenia; Kuchcinska, Agnieszka; Rehani, Madan M. (European Radiology, 2020)
Objectives: To have a global picture of the recurrent use of CT imaging to a level where cumulative effective dose (CED) to individual patients may be exceeding 100 mSv at which organ doses typically are in a range at which radiation effects are of concern METHODS: The IAEA convened a meeting in 2019 with participants from 26 countries, representatives of various organizations, and experts in radiology, medical physics, radiation biology, and epidemiology. Participants were asked to collect data prior to the meeting on cumulative radiation doses to assess the magnitude of patients above a defined level of CED.Results: It was observed that the number of patients with CED ≥ 100 mSv is much larger than previously known or anticipated. Studies were presented in the meeting with data from about 3.2 million patients who underwent imaging procedures over periods of between 1 and 5 years in different hospitals. It is probable that an additional 0.9 million patients reach the CED ≥ 100 mSv every year globally.Conclusions: There is a need for urgent actions by all stakeholders to address the issue of high cumulative radiation doses to patients. The actions include development of appropriateness criteria/referral guidelines by professional societies for patients who require recurrent imaging studies, development of CT machines with lower radiation dose than today by manufacturers, and development of policies by risk management organizations to enhance patient radiation safety. Alert values for cumulative radiation exposures of patients should be set up and introduced in dose monitoring systems.Key Points: • Recurrent radiological imaging procedures leading to high radiation dose to patients are more common than ever before. • Tracking of radiation exposure of individual patients provides useful information on cumulative radiation dose. • There is a need for urgent actions by all stakeholders to address the issue of high cumulative radiation doses to patients.